Genotyping microhaplotype markers through massively parallel sequencing. (December 2017) - Zhu, Jing; Chen, Peng; Qu, Shengqiu; Wang, Hui; Chen, Dan; Liang, Weibo; Zhang, Lin
Abstract: Mixture interpretation is challenging at present. Short tandem repeats (STR) and single nucleotide polymorphism (SNP) are still in mainstream in forensic genetics, but both of them are not good enough for mixture interpretation. Microhaplotype is a potentially polymorphic genetic marker. In this study, DNA mixtures were simulated at different mixing ratio, and microhaplotype markers were used to analyzing the mixtures through massively parallel sequencing (MPS).